Kislinsko-bazno ravnovesje - Jošt, Anton (Medicinski razgledi, 2002)
Acids are donors, while bases are acceptors of protons in solutions. Many various acids and bases are incorporated into organisms by everyday alimentation and cell metabolism, while the output routes are the respiratory system, kidneys and gastrointestinal system. The concentration of free protonsin the blood (expressed as pH value) is strictly regulated, as it has agreat impact on cell metabolism. There are many ways in which organisms defend themselves against harmful pH changes. The first line of defense is buffering, which takes place in both extra- and intracellular fluids; the second is regulation of elimination of acids and bases via the respiratory system (volatile acids) and kidneys (nonvolatile acids - sodium hydrogen carbonate). Many parameters can be determined from blood and urine samples, which can help diagnose and monitor patient acid-base disorders. Important measurements of urine include pH, urinary titrable acid and net acid excretionfor blood pH, hydrogen carbonate concentration and partial pressure of carbon dioxide. For further analysis of metabolic acidosis, base ex*ess, anion and osmolal gaps need to be determined. Acid-base disorders are divided into metabolic disorders with primary change in blood hydrogen carbonate concentration, and respiratory disorders with primary change in partial pressure of carbon dioxide. Acidosis causes a decrease in blood pH, while alkalosis causes an increase. The management of these disorders mainly consists of treatment of the underlying disease. In severe cases, it is also necessary to correct the pH status by adding acids or bases to the patient's blood.
Keywords: Acido-bazno ravnotežje; Acid-base equilibrium; Acid-base imbalance; Acidobazno ravnotežje, motnje; Acidoza; Diagnosis; Alkaloza; Therapy; Buffers; Pufri; Acidoza dihalna; Acidosis; Alkalosis; Alkaloza dihalna; fiziologija; Acidosis, respiratory; Alkalosis, respiratory; presnova; diagnostika; biokemija; acidobazno ravnotežje; motnje; zdravljenje